Infanticide of Newborns: A Comparative Study between Vietnamese Law and International Legal Frameworks - Khoat, Nguyen Van (Jurnal Cita Hukum, 2026)
Infanticide of newborns represents a particularly complex category of homicide, located at the intersection of criminal law, psychology, gender studies, and human rights. Many legal systems treat the killing of a newborn child by the mother under special legal provisions, recognising the unique physiological and psychological conditions surrounding childbirth. This article provides an in-depth analysis of the crime of killing a newborn child under Vietnamese criminal law, with a comprehensive comparison to selected international legal systems and international human rights standards. By examining the historical evolution, constituent elements of the offence, criminal liability, penalties, and underlying policy rationales, the article highlights similarities and differences between Vietnamese law and foreign legal approaches. The study further evaluates the compatibility of Vietnamese regulations with international human rights obligations and proposes recommendations for legal reform aimed at enhancing both child protection and maternal justice.